Slip Velocity Effect on Non-Newtonian Fluid Flow Over Moving Permeable Surface with Nonlinear Velocity and Internal Heat Generation/Absorption - Mohammad, Hossein Yazdi*; Hashim, I.; Moey, L. K.*; Sopian, K. (Praise Worthy Prize, 2014)
This work focuses on the steady slip boundary layer flow and heat transfer of a non-Newtonian power-law fluid over continuously nonlinear moving permeable surface at prescribed surface temperature including the effects of viscous dissipation and internal heat generation/absorption. The governing partial differential equations with the associated boundary conditions are first cast into a dimensionless form and then the reduced ordinary differential ones are solved numerically via Dormand-Prince pair and shooting method. Comparison of numerical results is made with the earlier published results under limiting cases. A comprehensive parametric study is carried out to investigate the effects of involved parameters of the problem. We have focused our attention on the evaluation of the local Nusselt number and the local skin friction coefficient. It is concluded, the rate of heat transfer increases with the nonlinear surface velocity index, surface temperature parameter, internal heat absorption, Prandtl number and suction